IMPACT OF FACULTY TRAINING ON ONLINE TEACHING READINESS DURING COVID-19 (The Research of Medical Science Review, 2025)
Background: The COVID-19 pandemic raised a challenging issue across the globe in educational institutions, specifically during the lockdown. All teaching and learning communities started adopting strategies to prevent the aftershocks if not addressed promptly and effectively. This study aimed to examine the extent of online readiness in teaching practices.Methods: The data was generated using Google Forms, applying a simple random sampling technique for this case study at ZU. By using multiple techniques of data collection, triangulation was executed to authenticate the information. Statistical and thematic analyses were performed to obtain the in-depth findings.Results: A total of 98 faculty members responded to the survey, containing 72 (73.5%) female and 26 (26.5%) male, with a composition of 15 (15.3%) senior faculty, 25 (25%) mid-career faculty, and 58 (59.2%) junior faculty members, whereas only 54 (55.1%) participated in the open-ended part of the questionnaire. Thematic analysis of the rich data (open-ended part) was conducted by identifying patterns or themes found grounded in the descriptive data.The six themes were Online Teaching Skills, Learning Management System (LMS), Connectivity Issues, Students' Engagement in Classroom, Students' Engagement in Clinical/Practical Issues, and Students’ Online Assessment.The obtained findings depict the tangible evidence of online teaching readiness as a result of the training courses offered.Conclusion: The data triangulation determined the degree of online teaching readiness as a result of faculty training. The amateur, being digital natives, found themselves more motivated and inclined towards online readiness as compared to the veteran, the digital immigrants.